Pleiotropic effect of the ABCA1 rs2230806 polymorphism in cardiovascular diseases: a literature review - A. A. Chernova; D. A. Nikulin; S. Yu. Nikulina; V. N. Maksimov (Российский кардиологический журнал, 2022)
Cerebrovascular accident (CVA) in patients with various cardiovascular diseases is a life-threatening complication, the development of which can be contributed by both environmental and genetic factors, the understanding of which is necessary to determine the tactics of treatment and predict the disease course. The article presents a brief review of studies on genetic predictors of CVA, in particular the association of the ABCA1 rs2230806 polymorphism and the risk of CVA in cardiovascular patients. Targeted studies of associations of the ABCA1 rs2230806 polymorphism with cerebrovascular diseases in the Russian Federation, except for studies at our university, could not be found.